Diverse Electron and Ion Acceleration Characteristics Observed Over Jupiter's Main Aurora. Issue 3 (15th February 2018) - Mauk, B. H.; Haggerty, D. K.; Paranicas, C.; Clark, G.; Kollmann, P.; Rymer, A. M.; Peachey, J. M.; Bolton, S. J.; Levin, S. M.; Adriani, A.; Allegrini, F.; Bagenal, F.; et al.
Abstract: Two new Juno‐observed particle features of Jupiter's main aurora demonstrate substantial diversity of processes generating Jupiter's mysterious auroral emissions. It was previously speculated that sometimes‐observed potential‐driven aurora (up to 400 kV) can turn into broadband stochastic acceleration (dominating at Jupiter) by means of instability. Here direct evidence for such a process is revealed with a "mono‐energetic" electron inverted‐V rising in energy to 200 keV, transforming into a region of broadband acceleration with downward energy fluxes tripling to 3, 000 mW/m 2, and then transforming back into a mono‐energetic structure ramping down from 200 keV. But a second feature of interest observed nearby is unlikely to have operated in the same way. Here a downward accelerated proton inverted‐V, with inferred potentials to 300–400 kV, occurred simultaneously with downward accelerated broadband electrons with downward energy fluxes as high as any observed (~3, 000 mW/m 2 ). This latter feature has no known precedent with Earth auroral observations. Key Points: Two new particle features are identified within the intense auroral acceleration regions at Jupiter demonstrating great diversity One feature supports a hypothesis that potential‐driven aurora can become unstable and convert over to broadband, stochastic acceleration The other feature contradicts that hypothesis and has no qualitative precedent within Earths' auroral acceleration regions